Effect of an opiate antagonist on the responses of circulating catecholamines and the renin-aldosterone system to acute sympathetic stimulation by hand-grip in man. - Lam, K; Grossman, A; Bouloux, P; Drury, P; Besser, G (1986)
The effect of naloxone on the neurohumoral responses to acute sympathetic stimulation by sustained hand-grip in normal man was investigated. Six normal males were studied fasting at 08.30 h, on two occasions at 7-day intervals, with each subject sustaining 30% of his maximal hand-grip on a hand dynamometer for 5 min. Naloxone (8 mg bolus) in 20 ml normal saline, or saline alone, was given 5 min before hand-grip in a randomised double-blind cross-over trial. Blood was sampled for plasma renin activity, serum aldosterone and plasma catecholamines. The study was repeated in the absence of hand-grip. Sustained hand-grip produced significant elevations in mean blood-pressure, circulating adrenaline, noradrenaline and aldosterone. Naloxone, which had no effect on basal catecholamines, plasma renin activity or aldosterone, significantly enhanced the responses in plasma adrenaline, plasma renin activity and serum aldosterone to hand-grip. The increments in blood pressure and noradrenaline were not affected. These results suggest that endogenous opioids modulate the response of the sympathoadrenal and renin-aldosterone systems to acute sympathetic stimulation by a mild stress in man.